Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Which of the following equations shows how substitution can be used to solve the following system of equations? [tex](y = 2x - 7 \\ 3 \times + 4y = 16[/tex]A: 3(2x-7) + 4y = 16B: 3x + 4(2x-7) = 16 C: y = -7D: 3x + 4y = 2x - 7

Sagot :

Answer:

B: 3x + 4(2x-7) = 16

Explanation:

The system of equations is

y = 2x - 7

3x + 4y = 16

To solve the system of equations by substitution, we need to substitute the first equation on the second equation. Since y = 2x - 7, we will replace y by 2x - 7 on the second equation, so

3x + 4y = 16

3x + 4(2x - 7) = 16

Therefore, the answer is:

B: 3x + 4(2x-7) = 16